Menyama Braya Sebagai Bentuk Keharmonisan Jemaat GKPB Galang Ning Hyang Abianbase Kecamatan Mengwi - Nia Desiska (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this paper is to describe menyama braya, which underlies harmony in the GKPB Galang Ning Hyang congregation. Menyama Braya is a local wisdom of the Balinese people which means helping one another. The research method used is qualitative phenomenological research and journal analysis. Menyama braya has great potential in maintaining harmony amid diversity. The Balinese people interpret this as loving others as they love themselves. This creates a congregation atmosphere full of harmony, peace, and joy.